Polyunsaturated Fatty Acids Modify the Gating of Kv Channels - Moreno, Cristina; Macias, Alvaro; Prieto, Angela; de la Cruz, Alicia; Valenzuela, Carmen (Frontiers in Pharmacology, 2012)
Polyunsaturated fatty acids (PUFAs) have been reported to exhibit antiarrhythmic properties, which are attributed to their capability to modulate ion channels. This PUFAs ability has been reported to be due to their effects on the gating properties of ion channels. In the present review, we will focus on the role of PUFAs on the gating of two Kv channels, Kv1.5 and Kv11.1. Kv1.5 channels are blocked by n-3 PUFAs of marine (docosahexaenoic and eicosapentaenoic acid, DHA and EPA) and plant origin (alpha-linolenic acid, ALA) at physiological concentrations. The blockade of Kv1.5 channels by PUFAs steeply increased in the range of membrane potentials coinciding with those of Kv1.5 channel activation, suggesting that PUFAs-channel binding may derive a significant fraction of its voltage sensitivity through the coupling to channel gating. A similar shift in the activation voltage was noted for the effects of arachidonic acid (AA) and DHA on Kv1.1, Kv1.2, and Kv11.1 channels. PUFAs-Kv1.5 channel interaction is time-dependent, producing a fast decay of the current upon depolarization. Thus, Kv1.5 channel opening is a prerequisite for the PUFA-channel interaction. Similar to the Kv1.5 channels, the blockade of Kv11.1 channels by AA and DHA steeply increased in the range of membrane potentials that coincided with the range of Kv11.1 channel activation, suggesting that the PUFAs-Kv channel interactions are also coupled to channel gating. Furthermore, AA regulates the inactivation process in other Kv channels, introducing a fast voltage-dependent inactivation in non-inactivating Kv channels. These results have been explained within the framework that AA closes voltage-dependent potassium channels by inducing conformational changes in the selectivity filter, suggesting that Kv channel gating is lipid dependent.